Increasing Production Capacity through Halal Product Process Assistance to SMEs in Bajeng District, South Sulawesi - Indriyani, Eka; Nursahwal, Nursahwal; Rahman, Nur Rahmadani; M, Nurhikma; Yaqin, Ainul; Sujiman, Ryan Anggara (DEDIKASI PKM, 2024)
The role of SMEs makes a major contribution to the economy in Indonesia. SMEs can grow and develop quickly because their basic nature is that they can be established with low personal capital from their owners. The current demands of information technology developments require SMEs to exist and be adaptive in utilizing digital applications. The obstacle currently facing SMEs is limited information to develop their business sector on a digital scale and get rewards for society. This research was carried out by first identifying the problems faced by SMEs and carrying out community service by providing training to increase SMEs production capacity. The training was held at the Panciro Village office, Bajeng District, Gowa Regency on September 13, 2023. The methods used included field surveys by collecting data on SMEs actors, interviews with SME actors, formulating problems, and determining solutions, namely by conducting SMEs seminars. The sampling method was purposive sampling focused on 27 culinary SMEs business actors spread across four hamlets in Panro Village: Kampung Parang Hamlet, Bontoramba Hamlet, South Bontoramba Hamlet, and Mattirobaji Hamlet.